Wordplay for kids : a sourcebook of poems, rhymes, and read-alouds - Wadham, Tim (ALA Editions, an imprint of the American Library Association, 2015)
Wadham provides resources for introducing younger children to literature in a public library or school library setting. By reading poems out loud together, and then introducing books and activities on the poem's theme, he noticed improved vocabulary and verbal skills, and a progression in the children's literacy skills. He also introduces the Shared Warmth program, which encourages families to read together.--